Representing the Database of Semantic Shifts by Zalizniak et al. from 2024 in Cross-Linguistic Data Formats (Computer-Assisted Language Comparison in Practice: Tutorials on Computational Approaches to the History and Diversity of Languages, 2024)
In this brief study, we show how the Database of Semantic Shifts, a large resource on semantic change and semantic motivation, can be represented in Cross-Linguistic Data Formats. The representation allows for a convenient quantitative analysis of the numerous annotations on semantic change and semantic motivation and for the integration of the database with additional resources on semantic change and semantic motivation that have been compiled independently in the last years.
Keywords: CLDF dataset; concept mapping; Database of Semantic Shifts; semantic shifts